Patogenesis demam berdarah dengue - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
ABSTRAK Many dengue haemorrhagic fever (DHF) pathomechanisms are still unlenci*K.'We--j:21i-2 "="1 pathogenesis of various DI-IF manifestations are believed to be immunologic processeszii.:.a.,:i Studies have confirmed many hypotheses, but the complexity of the problems leayunarty2.,!)